A retrospective analysis of the circumstantial factors contributing to drowning incidents reported in the South African media - de Beer, Willem (Division of Emergency Medicine, 2023)
The first consensus guidelines for the uniform reporting of drowning were published in 2003, and specifically call for the precipitating factor to be described. The aim of this study was to describe the precipitating factors contributing to fatal drowning incidents reported in the South African media between January 2017 and March 2021 through a retrospective analysis of the Lifesaving South Africa media report database. There were 767 fatal drowning incidents reported during this period. Two thirds (66%) of reported incidents occurred during spring and summer, and the majority occurred in coastal provinces. Weekends and public holidays accounted for the highest frequency of reported incidents. Forty percent of reported fatal drowning victims were children under the age of 16 years. Approximately half (48%) of fatal drowning victims were swimming at the time of the incident, 17% drowned following accidental entry into the water and 11% were boating or sailing at the time of the incident. Understanding the activity immediately preceding the drowning event allows for more efficient and context appropriate design of prevention interventions.